Chromium-Containing Traditional Chinese Medicine, Tianmai Xiaoke Tablet, for Newly Diagnosed Type 2 Diabetes Mellitus: A Meta-Analysis and Systematic Review of Randomized Clinical Trials. (7th March 2018) - Gu, Yuming; Xu, Xuemin; Wang, Zhe; Xu, Yunsheng; Liu, Xiuzhi; Cao, Lejun; Wang, Xueyang; Li, Zhengxin; Feng, Bo
Abstract : Objective. Chromium-containing traditional Chinese medicine Tianmai Xiaoke tablet (TMXKT) is approved for treating newly diagnosed type 2 diabetes mellitus (T2DM) in China. This review aimed to compile the evidence from randomized clinical trials (RCTs) and quantify the effects of TMXKT on newly diagnosed T2DM. Methods. Seven online databases were investigated up to March 20, 2017. The meta-analysis included RCTs investigating the treatment of newly diagnosed T2DM, in which TMXKT combined with conventional therapy was compared with placebo or conventional therapy. The risk of bias was evaluated using the Cochrane Collaboration tool. The estimated mean difference (MD) and the standardized mean difference were within 95% confidence intervals (CI) with respect to the interstudy heterogeneity. The outcomes were measured using fasting blood glucose (FBG), 2-h postprandial blood glucose (2hPG), glycosylated hemoglobin A1c (HbA1c), and body mass index (BMI) levels. Results. TMXKT combined with conventional therapy lowered FBG level (M D = - 0.68, 95% CI −0.90 to −0.45, P < 0.00001 ), 2hPG (M D = - 1.33, 95% CI −1.86 to −0.79, P < 0.00001 ), HbA1c (MD = −0.46, 95% CI −0.57 to −0.36, P < 0.00001 ), and BMI (MD = −0.77, 95% CI −1.12 to −0.41, P < 0.00001 ). Conclusions. TMXKT combined with conventional therapy is beneficial for patients with newly diagnosed T2DM. However, the effectiveness and safety of TMXKT are uncertain because of the limited number of trials and low methodological quality. Therefore, practitioners should be cautious when applying TMXKT in daily practice. Also, well-designed clinical trials are needed in the future.